Il “Saul” di Vittorio Alfieri - Paola Trivero (Altre Modernità, 2011)
My paper analyzes Vittorio Alifieri’s tragedy Saul. The author writes the tragedy after reading the Bible, and particularly Samuel’s first book. Alfieri is enthusiastic about the biblical text, thanks to its “sublime” theme and style, very useful for adapting the story as a tragedy. Alfieri creates Saul without betraying the spirit of the source text – he underlines the king of Israel’s ambivalent behavior toward his son-in-law David, whom he loves and hates at the same time. From this perspective, Saul is quite a different character from the other “tyrants” from Alfieri’s other tragedies. In his own words, the author finds in Saul «that uncertainty of the human heart, so magical; so, a man loving two loves opposite to one another, wants and does not want the very same thing. This uncertainty is one of the major secrets for generating emotion and suspension in a theatre». And Alfieri makes it. He himself plays Saul on stage, many times, since he considers him his “dearest” character – according to the author, in this character there is «everything, absolutely everything». Moreover, Saul has been staged with the most famous actors all along the Nineteenth and Twentieth century.